Thoracic wall metastases from nasopharyngeal carcinoma in a teenage boy: a case report - Asha'ari, Zamzil Amin (Elsevier, 2016)
We report an extremely rare case of nasopharyngeal carcinoma in a 14-year old boy presenting with neck and chest wall metastasis. Radiological and histological examinations established the diagnosis of nasopharyngeal carcinoma with non-keratinizing undifferentiated, WHO Type III form. He received 3 courses of chemotherapy followed by 35 cycles of radiotherapy. The primary site and the neck and chest wall metastases responded well with treatment. At 3 years follow up, the patient is still in a symptomfree and relapse-free state. Despite presenting late, juvenile onset WHO type 3 NPC showed a good response to chemoradiotherapy in our teenage patient.